Grow your own drugs easy recipes for natural remedies and beauty fixes - Wong, James (Reader's Digest Association, 2009)
Whether you're struggling with insomnia, the kids have eczema, or your partner is feeling under the weather, this book could have the answer. With easy recipes, ethnobotanist James Wong shows how to make simple creams, salves, teas and much, much more from the stuff growing in your window box, in your local grocery or garden center, or even in the sidewalk. Using the flowers, fruit, roots, trees, vegetables and herbs that are all around us James provides preparations to help relieve a whole range of common conditions, including acne, anxiety, cold sores and general aches and pains - plus great ideas for beauty treats such as bath bombs and shampoos. Inspired by his grandmother in Malaysia who taught him about the health-giving properties of plants, James uses his top class academic knowledge to show how easy - and cheap - it is to make creams, lotions, lozenges and more which can help relieve the symptoms of a variety of common complaints. He reveals how many plants contain the same active ingredients as over-the-counter drugs and chooses his Top 100 plants to grow or buy, complete with ideas for a whole range of uses. So unleash the power of plants and soothe the symptoms of everyday ailments the natural way.